The ecohealth assessment and ecological restoration division of urban water system in Beijing - Liu, Jingling (Ecotoxicology (London, England), 2009)
Evaluating six main rivers and six lakes in Beihuan water system (BWS) and diagnosing the limiting factors of eco-health were conducted for the ecohealth assessment and ecological restoration division of urban water system (UWS) for Beijing. The results indicated that Jingmi River and Nanchang River were in a healthy state, the degree of membership to unhealthy were 0.358, 0.392, respectively; while Yongding River, Beihucheng River, Liangma River, Tongzi River and six lakes were in an unhealthy state, their degree of membership to unhealthy were between 0.459 and 0.927. The order of that was Liangma > Beihucheng > Tongzi > Yongding > six lakes > Jingmi > Nanchang, in which Liangma Rivers of that was over 0.8. The problems of Rivers and lakes in BWS are different. Jingmi River and Nanchang River were ecotype limiting; Yongding River, Tongzi River and six lakes were water quality and ecotype limiting. Beihucheng River and Liangma River were water quantity, water quality and ecotype limiting. BWS could be divided into 3 restoration divisions, pollution control division including Yongding River, Tongzi River and six lakes; Jingmi River and Nanchang River were ecological restoration zone, while Beihucheng River and Liangma River were in comprehensive improvement zone. Restoration potentiality of Jingmi River and Nanchang River were higher, and Liangma River was hardest to restore. The results suggest a new idea to evaluate the impact of human and environmental factors on UWS